Antibacterial Modes of Herbal Flavonoids Combat Resistant Bacteria - Song, Lianyu; Hu, Xin; Ren, Xiaomin; Liu, Jing; Liu, Xiaoye (Frontiers in Pharmacology, 2022)
The increasing dissemination of multidrug resistant (MDR) bacterial infections endangers global public health. How to develop effective antibacterial agents against resistant bacteria is becoming one of the most urgent demands to solve the drug resistance crisis. Traditional Chinese medicine (TCM) with multi-target antibacterial actions are emerging as an effective way to combat the antibacterial resistance. Based on the innovative concept of organic wholeness and syndrome differentiation, TCM use in antibacterial therapies is encouraging. Herein, advances on flavonoid compounds of heat-clearing Chinese medicine exhibit their potential for the therapy of resistant bacteria. In this review, we focus on the antibacterial modes of herbal flavonoids. Additionally, we overview the targets of flavonoid compounds and divide them into direct-acting antibacterial compounds (DACs) and host-acting antibacterial compounds (HACs) based on their modes of action. We also discuss the associated functional groups of flavonoid compounds and highlight recent pharmacological activities against diverse resistant bacteria to provide the candidate drugs for the clinical infection.